PENGARUH MIKORIZA +MHB TERHADAP SERAPAN FOSFAT DAN DERAJAT INFEKSI AKAR BIBIT KOPI ARABIKA (Coffea arabica L.) - Desy Putri Islamiyah; Imam Mudakir; Pujiastuti Pujiastuti (Jurusan Pendidikan MIPA FKIP Universitas Jember, 2017)
Abstract: Giving mycorrhizae to increase phosphate uptake to arabica coffee seedlings. This research is laboratory experimental. The study was conductes for eight weeks. The purpose of this study was to examine the effect of mycorrhiza +MHB on phosphate uptake and degree of root infection of coffee seeds. This research used Complete Random Design (RAL) with four levels of 0 g (m0), 5 g (m1) 10 g (m2), 15 g (m3). The data obtained were analyzed using Anova and LSD advanced test. From the results of this study can be concluded that giving mycorrhiza +MHB significantly influence on phosphate uptake and degree of root infection of arabica coffee seedlings (Coffea arabica L.) Treatment with 15 g of mycorrhiza +MHB showed the best results on phosphate uptake and degree of root infection with other treatment. Keywords: Coffea arabica L., phosphate uptake, mycorrhiza, MHB.